Muerte de un periodista, Granada 1936 : Constantino Ruiz Carnero 1887-1936 / Francisco Vigueras ; prólogo de Ian Gibson - Gibson, Ian (1939-); Vigueras, Francisco (Serie Granada)
Bibliografía. Fuentes. Índices